Research into emissions of nitrogen oxides when converting the diesel engines to alternative fuels - Скалацька, Олена Віталіївна; Скалацька, О. В.; Скалацкая, Елена Витальевна; Skalatska, Olena V.; Криштопа, Святослав Ігорович; Криштопа, С. І.; Криштопа, Святослав Игоревич; Kryshtopa, Sviatoslav I.; Панчук, Мирослав Васильович; Панчук, М. В.; Панчук, Мирослав Васильевич; Panchuk, Myroslav V.; et al. (PC Technology Center, 2018)
We conducted theoretical and experimental research into emissions of nitrogen oxides in exhaust gases of the diesel engines, re-equipped for gas. The research is important because the emissions of nitrogen oxides in the exhaust gases are one of the biggest environmental problems at the present stage of development of designs for internal combustion engines. Therefore, reducing the emissions of nitrogen oxides in diesel engines by re-equipping them to gas fuel is an important task for specialists in design and operation of internal combustion engines. The result of theoretical research is the mathematical model that we constructed in order to calculate emissions of nitrogen oxides in the exhaust gases of diesel engines and the engines, converted to gas fuel. Based on experimental research, we have established dependences of emissions of nitrogen oxides in exhaust gases of the diesel engines, re-equipped for gas, on loading and the crankshaft rotation frequency. Studies have shown that diesel engines, which are converted to alternative gas fuel, reduce emissions of nitrogen oxides in the exhaust gases in a range from 13.9 % to 47.1 % depending on engine rotation and load. The results obtained make it possible to reduce the emissions of harmful substances in exhaust gases of automobile engines and optimize design of the systems for exhaust gases recirculation

Розроблена математична модель роз-рахунку викидів оксидів азоту у відпрацьо-ваних газах дизельних двигунів та двигунів переобладнаних на газове паливо. Виконані в лабораторних умовах експерименталь-ні дослідження дизельного двигуна моделі X17DTL автомобіля Опель Астра на вики-ди оксидів азоту у відпрацьованих газах дизельного двигуна та двигуна конверто-ваного на газове паливо
Kryshtopa S. Research into emissions of nitrogen oxides when converting the diesel engines to alternative fuels / Kryshtopa S., Panchuk M., ... Skalatska O. // Eastern-European Journal of Enterprise Technologies. - № 1(10-91). - PC Technology Center, 2018. – P. 16–22.
Keywords: alternative fuels; diesel engine; nitrogen oxides; engine re-equipped for gas fuel; льтернативные топлива; дизельный двигатель; оксиды азота; конвертация двигателя на газ; Research Subject Categories::TECHNOLOGY